PENGGUNAAN TANAH MELILING UNTUK PEMBENTUKAN STONEWARE KI DAN ANALISIS HARGA POKOK PRODUKSI DENGAN STANDAR SEBAGAI DASAR PENGAMBILAN KEPUTUSAN BISNIS - I Nyoman Normal; Wiryawan Suputra Gumi (Forum Manajemen, 2012)
Abstracts Meliling blend is a blend that come from Meliling (Tabanan) that fulï¬ ll laboratory Standard as raw material of stoneware, so that it could use to produce stoneware KI at UPT PSTKP Bali. The analysis of cost of goods manufactured stoneware KI use standard costing. Standard costing is predetermine cost whichmust expenditured to produce unit product or to paid special operation. Standard cost systems was design to cost control, be important tool to evaluate judgement that was setting. The aims of this research were : (1) To knew the Meliling blend can use to produce stoneware KI; (2) To knew cost of good manufactured stoneware K1 bystandard cost systems; and (3) To knew ussefull of standard costing stoneware KI for business decision. The research results shew that : (1) The Meliling blend can use to produce stoneware KI by the mixing with the other material, that is : Meliling blend 50%, kaolin 20%, Lodoyo feldspar 20%, ball clay 8%, and talcum powder 2%; (2)Cost of good manufactured stoneware K1 by standard cost systems was Rp 2.799,25 each kg, but its actual cost was Rp 2.659,47 each kg. Cost of good manufacturedstoneware by the standard cost systems was bigger about Rp 139,77 than actual cost systems, because there were different into computation ways of raw material, different loading of direct labour cost, and different loading of manufacturing overhead cost (variable and ï¬ xed);and (3) Standard cost applicationof stoneware KI is very useful into business decision making for stoneware product, that is : a) As a tool of control, b) As a tool of decision making, c) As a tool of rasional cost measurement, and d) Asa tool of recording cost economizing.